ISSUES OF CONTROVERSIAL PRACTICE REFERRING TO THE CRIME OF FALSE TESTIMONY - Mirela GORUNESCU (Challenges of the Knowledge Society)
The crime of false testimony is one of the crimes which are traditionally found in our criminal legislation, the judicial practice recording also specific situations which required the application of the incrimination text which defined this crime. It can be considered that we are dealing with a crime which can no longer present any difficulties in relation to the interpretation and application of the incrimination norm with regard to the particular deeds committed. However, many elements are still encountered with respect to the interpretation of the incrimination norm, which generate different solutions of application, a fact which –in accordance with the rigors of the criminal law- is not to be desired. This study approaches two of these issues, namely the juridical significance of the refusal of the person heard as a witness to give any statements in such capacity and, on the other hand, the possibility of the realization of a formal concurrence of crimes when the person summoned as a witness, through his/her false or incomplete statement intends to create a situation more favorable to a person regarded by the factual situation.